615 ≈ 600 (nearest hundred)
Due to the Triangle Angle Sum Theorem, we know that the sum of the interior angles of a triangle equals 180 degrees, therefore,
180 = m<1 + m<2 + m<3
180 - m<3 = m<1 + m<2
But, we also know that m<4 + m<3 = 180 degrees.
180 = m<3 + m<4
180 - m<3 = m<4
Both m<4 and m<1 + m<2 equals 180 - m<3
m<4 = m<1 + m<2
Answer: Yes my bestfriend
Step-by-step explanation:
Answer:
see explanation
Step-by-step explanation:
Differentiate using the product rule
Given y = f(x)g(x), then
= f(x). g'(x) + g(x). f'(x)
here f(x) =
⇒ f'(x) = ![e^{x}](https://tex.z-dn.net/?f=e%5E%7Bx%7D)
g(x) = cosx ⇒ g'(x) = - sinx
Hence
=
(- sinx) + cosx ![e^{x}](https://tex.z-dn.net/?f=e%5E%7Bx%7D)
=
cosx -
sinx
Answer:
1,-4
Step-by-step explanation:
I hope it helps because we did that in class